The Adult Learner’s Quest: W.E.B. Du Bois As Vicarious Mentor - Don Hofford (Adult Education Research Conference, 2006)
The intentional adult learner is intellectually and emotionally in a perpetual “act of seeking.” The search is for purpose, meaning, humanistic dialogue, self-awareness, creative adventure, and life-affirming experiences. This act of seeking makes the on-going, existential life journey an educational commitment; a continuing involvement with both abstract ideas and concrete reality. Age dims the eyes, not visionary possibilities; slows the reflexes, not the reflective skill that helps define the person as a thinking, questioning, questing being.